Canine chronic enteropathy—Current state-of-the-art and emerging concepts - Jergens, Albert E.; Heilmann, Romy M. (Frontiers in Veterinary Science, 2022)
Over the last decade, chronic inflammatory enteropathies (CIE) in dogs have received great attention in the basic and clinical research arena. The 2010 ACVIM Consensus Statement, including guidelines for the diagnostic criteria for canine and feline CE (Washabau et al., 2010), was an important milestone to a more standardized approach to patients suspected of a CE diagnosis. Great strides have been made since understanding the pathogenesis and classification of CE in dogs, and novel diagnostic and treatment options have evolved. New concepts in the microbiome-host-interaction, metabolic pathways, crosstalk within the mucosal immune system, and extension to the gut-brain axis have emerged. Novel diagnostics have been developed, the clinical utility of which remains to be critically evaluated in the next coming years. New directions are also expected to lead to a larger spectrum of treatment options tailored to the individual patient. This review offers in-sights into emerging concepts and future directions proposed for further CE research in dogs for the next decade to come.